2017
DOI: 10.1038/labinvest.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

The master role of microphthalmia-associated transcription factor in melanocyte and melanoma biology

Abstract: Certain transcription factors have vital roles in lineage development, including specification of cell types and control of differentiation. Microphthalmia-associated transcription factor (MITF) is a key transcription factor for melanocyte development and differentiation. MITF regulates expression of numerous pigmentation genes to promote melanocyte differentiation, as well as fundamental genes for maintaining cell homeostasis, including genes encoding proteins involved in apoptosis (eg, BCL2) and the cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
200
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(208 citation statements)
references
References 99 publications
(150 reference statements)
6
200
0
2
Order By: Relevance
“…Proteins that activate or repress the expression of MITF‐M are potential gene candidates. For instance, FOXD3, POU3F2, ALX3, TNF‐α, and TGF‐ß can reduce MITF‐M levels; in contrast, genes involved in cAMP‐CREB, Wnt, or MAPK signaling pathways can increase MITF expression . Furthermore, post‐translational modifications (eg, ubiquitination, phosphorylation) and chromatin complexes that mediate epigenetic remodeling (eg, DNA methylation, histone modifications) contribute to MITF regulation .…”
Section: Perspectives Areas Of Uncertainty and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins that activate or repress the expression of MITF‐M are potential gene candidates. For instance, FOXD3, POU3F2, ALX3, TNF‐α, and TGF‐ß can reduce MITF‐M levels; in contrast, genes involved in cAMP‐CREB, Wnt, or MAPK signaling pathways can increase MITF expression . Furthermore, post‐translational modifications (eg, ubiquitination, phosphorylation) and chromatin complexes that mediate epigenetic remodeling (eg, DNA methylation, histone modifications) contribute to MITF regulation .…”
Section: Perspectives Areas Of Uncertainty and Conclusionmentioning
confidence: 99%
“…The MITF gene encodes a basic helix-loop-helix leucine zipper (b-HLH-Zip) dimeric nuclear transcription factor essential for the survival, migration, proliferation, and differentiation of multiple cell lines. 100,101 Nine unique promotor-exon units have been identified and are important in synthesizing several isoforms with distinct 5′ exons. The M-isoform is expressed exclusively in the melanocytes lineage.…”
mentioning
confidence: 99%
“…Among those, the M‐isoform of MITF (MITF‐M) is expressed almost exclusively in melanocytes (Fuse, Yasumoto, Suzuki, Takahashi, & Shibahara, ), although it has also been detected in retinal pigment epithelium (Bharti, Liu, Csermely, Bertuzzi, & Arnheiter, ; Masuda & Esumi, ) and likely in mouse olfactory bulb projection neurons (mitral cells and tufted cells) (Ohba, Takeda, Yamamoto, & Shibahara, ). Besides CREB mentioned previously, multiple other transcription factors are involved in the regulation of MITF‐M at the transcriptional level, including paired box gene 3 (PAX3), SRY (sex‐determining region Y)‐box 10 (SOX10), lymphoid enhancer‐binding factor 1 (LEF1 or TCF), one cut domain 2 (ONECUT‐2), and MITF itself (reviewed in Kawakami & Fisher ). PAX3 functions synergistically with SOX10 to activate and induce MITF transcription (Bondurand et al., ).…”
Section: Central Determinants Of Melanocytic Pigmentationmentioning
confidence: 99%
“…The protein inhibitor of activated STAT3 (PIAS3), which causes sumoylation of MITF, represses MITF activity by inhibiting its DNA-binding ability (Levy, Nechushtan, & Razin, 2002;Miller, Levy, Davis, Razin, & Fisher, 2005). In the past, various studies have revealed other proteins that potentially repress MITF transcription, such as FOXD3, POU3F2, transforming growth factor β (TGFβ), and ALX3 through suggested mechanisms (reviewed in Kawakami & Fisher 2017).…”
Section: Microphthalmia-associated Transcription Factormentioning
confidence: 99%
“…Thus, the ability to repress EGR1 inhibits multiple means of damage from cardiac infarct, including subsequent inflammation, apoptosis, and autophagy. Furthermore, in a mouse model of lung transplant, EGR1 deletion improved graft function by attenuating neutrophil recruitment [152]. Of note, downregulating EGR1 in cardiomyocytes also appears to be beneficial.…”
Section: Wt1 and Egr1 In Cardiovascular And Pulmonary Pathophysiologymentioning
confidence: 99%